Prospects for the Use of Ash and Slag Waste in the Construction of Road Pavement - Andrii Bieliatynskyi; Shilin Yang; Valerii Pershakov; Oleksandra Akmaldinova; Kateryna Krayushkina; Meiyu Shao (The Baltic Journal of Road and Bridge Engineering)
The relevance of the subject matter is conditioned by the importance of resolving the issues of practical use of ash and slag waste to create a high-quality road surface. The aim of the study is to determine the main promising areas for the use of ash and slag waste in creating a reliable road surface structure during roadway repair. The leading approach in this study is the systematic analysis of the entire complex of issues submitted for consideration, in the context of assessing the importance of the prospects for the practical use of waste in road construction to create a high-quality road surface and the prospects for reducing the cost of its maintenance and possible repair. It has been found that the practical use of ash and slag waste can significantly increase the strength of the road surface and increase its service life. Also, it is stated that the use of ash and slag mixture allows for achieving a significant reduction in the cost of building materials. It is concluded that the activating additives should be introduced to reduce cement consumption.